Politics and Jobs : the Boundaries of Employment Policy in the United States. - Weir, Margaret (Princeton University Press, 1992)
Americans claim a strong attachment to the work ethic and regularly profess support for government policies to promote employment. Why, then, have employment policies gained only a tenuous foothold in the United States? To answer this question, Margaret Weir highlights two related elements: the power of ideas in policymaking and the politics of interest formation. Rather than seeing policy as a straightforward outcome of public preferences, she shows how ideas frame the.